Anthropometric and functional indicators of athletes with different types of body constitution - Holiaka, S.; Hluhov, I. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to determine the main anthropometric indicators, the level of the functional state of the cardiovascular and respiratory systems of athletes, depending on the type of constitution of their body.